Seroprevalence of Cytomegalovirus and Rubella among Women seeking Antenatal care and the implications of Socio-demographic, Obstetric and Clinical determinants - Abdullah S.H. Alruwaili; Santhanamari Thiyagarajan (The Bioscan, 2025)
Vertical transmission of maternal infections of Cytomegalovirus (CMV) and Rubella virus (RV) have serious fetal and neonatal outcomes. A cross sectional study was conducted with 471 pregnant women attending antenatal clinics in Chennai city to determine the seroprevalence of CMV and RV and the contributing factors. Serum samples of the study population were screened for the IgM and IgG antiviral antibodies by ELISA. The seroprevalence of CMV and RV were 87% and 56% respectively. While the rate of past (IgG) and primary (IgM) infections were higher for RV, the CMV caused more active infections (IgM+IgG). Significant sociodemographic characteristics associated with CMV and RV infections were pregnancy in advanced age (OR=0.916, CI=0.712-1.861, P=0.028), low education level (OR=1.792, CI=1.212-2.996, P=0.039) and living in rural areas (OR=2.314, CI=1.492-3.237, P=0.028). The infection during first pregnancy (OR=0.827, CI=0.581-0.996, P=0.036), 1st trimester (OR=1.496, CI=0.998-1.853, P=0.015) and high rate of miscarriage (OR=2.958, CI=2.212-3.826, P=0.032) were the recorded obstetric risk factors. Clinical features significantly attributed to the infections were abnormal BMI (OR=0.861, CI=0.468-1.221, P=0.028), abnormal hemoglobin level (OR=0.862, CI=0.542-0.972, P=0.044) and history of jaundice (OR=0.383, CI=0.128-0.539, P=0.021). The study suggested the need for regular serological surveillance, vaccination and awareness education to prevent the infections caused by CMV and RV.